A Rare Mullerian Duct Anomaly Not Included in the Classification System by the American Society for Reproductive Medicine - Shereene J. Brown; Shawky Z. A. Badawy (Hindawi Limited, 2013)
This is a case report of a 37-year-old female with a uterine septum (two cavities), a normal single fundal contour, two cervices, and a longitudinal vaginal septum. This is a rare finding that is not described in the current classification system by the American Society for Reproductive Medicine.